The effect of the Bilateral Integration exercise program on the cognitive functioning of pupils with moderate intellectual disabilities - Koper, Magdalena; Lewandowska, Magdalena; Rękosiewicz, Małgorzata (Frontiers in Psychiatry, 2024)
Children with intellectual disability tend to exhibit lower performance in fundamental movement skills, such as locomotor skills, object control skills, and balance, compared to their typically developing peers. Evidence suggests that physical activity programs tailored for individuals with intellectual disabilities can positively influence the development of their motor skills. Similar to typically developing children, physical activity in children with intellectual disabilities stimulates not only physical development, but also brain function, resulting in cognitive benefits. However, the extent of physical activity's impact on the cognitive functioning of this population remains insufficiently explored. The aim of our study was to assess the effectiveness of a motor exercise program based on the Bilateral Integration method implemented for pupils with moderate intellectual disabilities.The sample consisted of 27 pupils with moderate intellectual disability (13 in the intervention group and 14 in the control group) from two special schools in Poland. Pupils in the intervention group participated in a modified version of the Bilateral Integration School Program -a 26-week physical activity program that included both individual and group sessions. The assessment of cognitive functioning, using the Fifth Edition of the Stanford-Binet Intelligence Subtests, was conducted over three time points in both groups: a pre-test before the intervention (T1), a post-test after the intervention phase end (T2) and a follow-up assessment three months after the post-test (T3).Results: Significant effects of the intervention compared to the control group were observed in certain cognitive variables. Repeated measures ANOVA revealed a significant group-by-time interaction for the Nonverbal Visual-Spatial Processing score, Nonverbal Working Memory score, as well as Verbal Fluid Reasoning.The original program based on the Bilateral Integration method proved effective for pupils with moderate intellectual disability. Preliminary results indicate improvements in cognition, particularly in working memory and visual-spatial processing. Further studies are necessary to assess the program's efficacy comprehensively.